2021
DOI: 10.3390/polym13111867
|View full text |Cite
|
Sign up to set email alerts
|

A Suggested Vacuum Bagging Process for the Fabrication of Single-Walled Carbon Nanotube/Epoxy Composites That Maximize Electromagnetic Interference Shielding Effectiveness

Abstract: We designed and tested a manufacturing process that resulted in the formation of composites with maximized electrical conductivity and optimized electromagnetic interference (EMI) shielding effectiveness (SE) properties. Single-walled carbon nanotube (SWCNT) paper, which is a microscopic aggregate of van der Waals force interaction, was impregnated with semi-cured epoxy to make SWCNT prepregs. These prepregs were completely cured into SWCNT/epoxy composites. Fabricating and curing processes were executed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…With the rapid development of communications and internet technologies, electromagnetic interference (EMI) has emerged as a serious threat to the stable functioning of electronic devices [ 5 , 6 , 7 , 8 ]. The application of CPCs with nanofillers is one of the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of communications and internet technologies, electromagnetic interference (EMI) has emerged as a serious threat to the stable functioning of electronic devices [ 5 , 6 , 7 , 8 ]. The application of CPCs with nanofillers is one of the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Ke et al [22] prepared a novel film adhesive for the bonding of carbon fiber reinforced polymer (CFRP) composites to steel substrates, and the results showed that there was a stronger interfacial bond in the adhesive layer and better adherence than in the intralaminar of CFRPs. The development of technology put forward functional requirements for adhesive materials, such as adhesives with thermal conductivity [23][24][25][26], wave absorption [27], and electromagnetic shielding properties [28,29]. Researchers developed a series of functional adhesives to meet the needs of different fields [30].…”
Section: Introductionmentioning
confidence: 99%